The Role of Involvement in Social Networks and Prudence in Establishing the Persistence of Online Customers Who Have Experienced Fraud - Aneke Dewi Rahayu (Universitas Muhammadiyah Sidoarjo, 2015)
Internet network had been developed over the years and its utilization has also increased and extended to various fields including midwives venturing into online business. Online transaction can be performed through digital media and do not require a direct meeting between the seller and the buyer. Online purchase is called with an e-commerce where the system continues to experience growth. As this growth there is a lot of cheating and fraud. The number does not decrease the negative impact of buying interest someone through e-commerce. There are two variables are taken into consideration, namely the emergence of persistent involvement in social networks and the prudence of a person due to lack of trust after fraud. The purpose of this study was to determine the effect of a person's involvement in social networks and caution against the persistence of online customers who have experienced fraud. Methods of analysis using path analysis with AMOS program. The results of this study are involved in social networking direct or indirect effect on the variable persistence through prudential variable.